Migration of noble gas tracers at the site of an underground nuclear explosion at the Nevada National Security Site. (November 2019) - Johnson, C.; Aalseth, C.E.; Alexander, T.R.; Bowyer, T.W.; Chipman, V.; Day, A.R.; Drellack, S.; Fast, J.E.; Fritz, B.G.; Hayes, J.C.; Huckins-Gang, H.E.; Humble, P.; et al.
Abstract: As part of an underground gas migration study, two radioactive noble gases ( 37 Ar and 127 Xe) and two stable tracer gases (SF6 and PFDMCH) were injected into a historic nuclear explosion test chimney and allowed to migrate naturally. The purpose of this experiment was to provide a bounding case (natural transport) for the flow of radioactive noble gases following an underground nuclear explosion. To accomplish this, soil gas samples were collected from a series of boreholes and a range of depths from the shallow subsurface (3 m) to deeper levels (~160 m) over a period of eleven months. These samples have provided insights into the development and evolution of the subsurface plume and constrained the relative migration rates of the radioactive and stable gas species in the case when the driving pressure from the cavity is low. Analysis of the samples concluded that the stable tracer SF6 was consistently enriched in the subsurface samples relative to the radiotracer 127 Xe, but the ratios of SF6 and 37 Ar remained similar throughout the samples. Highlights: Stable and radioactive tracer gases were injected into a historic nuclear test chimney. Tracer sampling conducted for 11 months at multiple locations around site. Dilutions of 37 Ar and SF6 were similar while 127 Xe was more dilute. SF6 was found to be a more accurate surrogate tracer than PFDMCH (C8 F16 ).